The Impact of South Jakarta Metro Police HR Management Practices and the Perception of Organizational Support for Organizational Commitment - Alfano Ramadhan; Basir S.; Surya Darma (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This research aimed to investigate the influence of human resource management practices on organizational commitment, with perceived organizational support serving as a moderating variable, at the South Jakarta Metro Police. This study applied a quantitative research method using a questionnaire as a data collection material which was analyzed with the help of SPSS version 22 software. The sample in this study was 93 respondents. This study is a rather basic attempt to investigate the relationship between employees' perceptions of HRM practices, organizational support, and their attitudes (in the form of organizational commitment). According to the results of the current study, employees' perceptions on how seriously their organization takes HRM procedures can be used as a reliable indicator of their commitment to the organization. Although it is expected that this practice has an indirect effect on commitment via perceived organizational support, only two of the three practices (in the forms of career development and performance appraisal) were found to be significant. As such, more research utilizing various HRM Practices is required, as the current findings are not fully promising.